The Application of Three-Dimensional Technologies in the Improvement of Orthopedic Surgery Training and Medical Education Quality: A Comparative Bibliometrics Analysis - Shi, Jian; Cavagnaro, María José; Xu, Shaokang; Zhao, Mingyi (Frontiers in Bioengineering and Biotechnology, 2022)
Orthopedics is a medical specialty that focuses on the clinical treatment and care of the musculoskeletal system. The education of orthopedics is often serious and difficult because of the high technical requirements, complicated anatomical knowledge and long study process. However, medical students or junior residents rarely have the opportunity to see such orthopedic surgery or attend preclinical practice, which limits the opportunities for training clinicians. Hopefully, with the increasing use of three-dimensional (3D) technologies in medical teaching, this situation can be alleviated. In this study, we demonstrate that different 3D technologies can effectively simulate orthopedic surgery with very high accuracy. We carefully evaluated the use of 3D technologies in primary medical teaching and proposed a vision for the future. We searched and screened 3997 publications from the WoSCC on Oct 22, 2021 with (trauma) AND ((education) OR (training) OR (teaching) OR (learning)) AND ((3D) OR (Three Dimensional)), (Joint) AND ((education) OR (training) OR (teaching) OR (learning)) AND ((3D) OR (Three Dimensional)), (spine) AND ((education) OR (training) OR (teaching) OR (learning)) AND ((3D) OR (Three Dimensional)) as the search strategy. Then, we eliminated the publications irrelevant to “orthopedics” AND/OR “orthopaedic” , the final number of publications are 440 for trauma surgery, 716 for joint surgery and 363 for spine surgery, a visual display of comprehensive information analysis was made by VOSviewer. Next, we read and analyzed retrieved articles extensively according to the selection criteria, 11 high cited publications on three major branches of orthopedics were chosen. The extracted data included the authors, purpose, methods, results and benefits/limitations. The evaluation of these studies directly and objectively proved the superiority of 3D technologies in orthopedics. Furthermore, the material usage and strength of 3D technologies can be closer to the real situation, which will help improve their effectiveness in teaching. We hope that more relevant studies will be conducted to continue examining the effects of 3D technologies on orthopedic medical education, and we hope that this technique can be more widely used in the clinical teaching of orthopedics to train clinicians on how to address such problems more quickly and efficiently.